The Effect of Taxpayer Awareness and Service of Regional Revenue Service Employees on PBB-P2 Taxpayer Compliance in Sidoarjo During the Covid 19 Pandemic: Pengaruh Kesadaran Wajib Pajak dan Pelayanan Pegawai Dinas Pendapatan Daerah Terhadap Kepatuhan Wajib Pajak PBB-P2 di Sidoarjo Pada Masa Pandemi Covid 19 - Endah Hermawan Budianti; Nurasik Nurasik (Academia Open, 2021)
This study aims to analyze the effect of taxpayer awareness and service of tax employees on taxpayer compliance. The sampling method used is accidental sampling. The sample in this study amounted to 101 samples. The data used is secondary data. The data analysis method used in this study is Multiple Linear Regression with SPSS 23. The results of this study indicate that taxpayer awareness has an effect on taxpayer compliance. The higher the level of awareness of taxpayers, the better understanding and implementation of tax obligations so as to increase compliance. Tax Employee Service Affects Taxpayer Compliance. Taxpayer compliance in fulfilling the obligation to pay taxes depends on how the tax officer provides the best quality of service to taxpayers.